Hume and the Tractatus on "cause/effect", "I" and "is/ought" - Alejandro (Analysis. Journal of Philosophical Research, 2021)
In this essay I propose to make the point that there are three philosophical topics in relation to which Hume and Wittgenstein defend basically the same position. On the other hand, however, I must point out ab initioque the rapprochement and convergence that can be discerned between them are practically tangential and cannot be carried too far for the simple reason that they arrive at the common position by entirely different routes. Our task, therefore, will be to show how the coincidence between them occurs and what lessons we can draw from that confluence. The issues I have in mind are the cause/effect relation, the nature of the "I" and the "is/ought" question, that is, what went down in history as ’Hume’s Guillotine’. Translated with www.DeepL.com/Translator (free version)